2009
DOI: 10.1002/smll.200800814
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Driven Self‐Assembled Network of Antidots in Complex Oxide Thin Films

Abstract: Structural strain due to lattice mismatch is used to promote the formation of a self-assembled network of antidots in highly epitaxial La(2/3)Sr(1/3)MnO(3) thin films grown on (001) oriented SrTiO(3) substrates by radiofrequency magnetron sputtering. Size, depth, and separation between antidots can be controlled by changing deposition parameters and the miscut angle of the substrate. This morphology exhibits a remarkable magnetic anisotropy and offers unique opportunities for versatile nanostencils for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…In a demonstration of an interesting and unusual heteroepitaxial film morphology resulting from MS growth, Konstantinovic et al [277] have shown that La 0.67 Sr 0.33 MnO 3 grown on misoriented SrTiO 3 (001) nucleates as nanoscale craters (or ''antidots'') that are aligned along terraces. Figure 7 shows AFM images for both the substrates (panels 1) and films (panels 2) for two extents of miscut: 0.278 (mean terrace width ¼ 86 nm) (a), and 0.128 (mean terrace width ¼ 186 nm) (b).…”
Section: Magnetron Sputteringmentioning
confidence: 98%
See 1 more Smart Citation
“…In a demonstration of an interesting and unusual heteroepitaxial film morphology resulting from MS growth, Konstantinovic et al [277] have shown that La 0.67 Sr 0.33 MnO 3 grown on misoriented SrTiO 3 (001) nucleates as nanoscale craters (or ''antidots'') that are aligned along terraces. Figure 7 shows AFM images for both the substrates (panels 1) and films (panels 2) for two extents of miscut: 0.278 (mean terrace width ¼ 86 nm) (a), and 0.128 (mean terrace width ¼ 186 nm) (b).…”
Section: Magnetron Sputteringmentioning
confidence: 98%
“…[265][266][267][268][269][270][271][272][273][274][275][276][277] As an example of the interesting and potentially useful physics that has been gleaned from studies of oxides grown by sputtering, we consider the observation of a giant planar Hall effect in epitaxial doped manganites. The planar Hall effect occurs in magnetic materials when the resistivity depends on the angle between the direction of current flow and the magnetization, the effect being otherwise known as anisotropic magnetoresistance.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…A careful selection of the growth conditions of LSMO films on top of STO substrates with well defined terrace-step morphology allows obtaining variety of long-range ordered nanostructured LSMO thin films [8,9]. The substrates are typically cut at a vicinal angle and their surface present atomic-height steps, which can induce inherent growth instability at the step edges during film growth playing a crucial role in the final morphology of the films.…”
Section: Resultsmentioning
confidence: 99%
“…The tendency of some oxides towards self-organized growth, forming regular arrays of 3D uniform structures, offers enormous potential for the preparation of nanotemplates that can be used for the fabrication of long range ordered nanostructured systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be explained by the lattice mismatch that is larger on LSAT (−1.5%) than on SrTiO 3 (−0.6%), although the epitaxial strain is in-plane compressive in both cases. The in-plane compressive strain can favor nanoislands formation, whereas in-plane tensile strain can favor nanopits formation, as shown in some epitaxial (La,Sr)MnO 3 films grown on SrTiO 3 (001) surface by sputtering [66]. Epitaxial growth of films with high surface energy may lead to 3D growth of nanostructures with surface facets of lower energy.…”
Section: Interface Structure and Energymentioning
confidence: 99%